2021
DOI: 10.7554/elife.64506
|View full text |Cite
|
Sign up to set email alerts
|

Pruriception and neuronal coding in nociceptor subtypes in human and nonhuman primates

Abstract: In humans, intradermal administration of β-alanine (ALA) and bovine adrenal medulla peptide 8–22 (BAM8-22) evokes the sensation of itch. Currently, it is unknown which human dorsal root ganglion (DRG) neurons express the receptors of these pruritogens, MRGPRD and MRGPRX1, respectively, and which cutaneous afferents these pruritogens activate in primate. In situ hybridization studies revealed that MRGPRD and MRGPRX1 are co-expressed in a subpopulation of TRPV1+ human DRG neurons. In electrophysiological recordi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 58 publications
5
27
1
Order By: Relevance
“…This is consistent with previous studies that have shown species differences in expression of pruritogen receptor genes such as the IL31 receptor (73). It is also consistent with a recent study comparing macaque and human DRG expression of pruritogen receptors MRGRPD and MRGPRX1 that demonstrated co-expression with TRPV1 (80). This contrasts with mouse experiments where Mrgprd is expressed by a subset of neurons that are devoid of Trpv1 (81).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies that have shown species differences in expression of pruritogen receptor genes such as the IL31 receptor (73). It is also consistent with a recent study comparing macaque and human DRG expression of pruritogen receptors MRGRPD and MRGPRX1 that demonstrated co-expression with TRPV1 (80). This contrasts with mouse experiments where Mrgprd is expressed by a subset of neurons that are devoid of Trpv1 (81).…”
Section: Discussionsupporting
confidence: 92%
“…We detected flare reactions, one of the hallmarks of HIS-induced CMi activation, after injections of BAM8–22 and ET-1 that were only slightly smaller than the HIS-induced flare, whereas β-ALA did not induce such a reaction. This is in good agreement with previous results from our own and other groups that delivered these chemicals via intradermal microinjection 6 , 8 , 45 47 , but differs from studies that administered ET-1 superficially by iontophoresis or BAM8–22 focally into the skin using inactivated cowhage spicules 5 , 48 . The lack of a flare response in the latter studies might indicate that CMi activation and flare reaction after injection of ET-1 or BAM8–22 potentially constitute an indirect effect caused by a pruritogen-induced HIS release from skin mast cells as one plausible scenario.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, if BAM8–22 is injected and thus delivered deeper into the skin, a HIS-dependent flare develops that does not add to the direct BAM8–22-dependent itch. In agreement with this notion, we could not detect additive effects on itch when we co-injected supra-threshold amounts of BAM8–22 and HIS 8 . Collectively our study substantiates that BAM8–22, β-ALA and ET-1 induce itch in humans via HIS-independent (BAM8–22, β-ALA) or only partially HIS-independent (ET-1) mechanisms.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations